Epigallocatechin 3-gallate attenuates arthritis by regulating Nrf2, HO-1, and cytokine levels in an experimental arthritis model - Karatas, Ahmet; Dagli, Adile Ferda; Orhan, Cemal; Gencoglu, Hasan; Ozgen, Metin; Sahin, Nurhan; Koca, Suleyman Serdar (Wiley, 2020)
Epigallocatechin 3-gallate (EGCG) is a polyphenol that has been shown to have antioxidant and anti-inflammatory effects. In this study, collagen-induced arthritis (CIA) model, in Wistar albino rats, was used to elucidate the effect of EGCG on pathogenetic pathways in inflammatory arthritis. The levels of serum TNF-alpha, IL-17, malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx); the expression levels of tissue heme oxygenase-1 (HO-1) and nuclear factor erythroid 2-related factor 2 (Nrf2); histopathologically, perisynovial inflammation and cartilage-bone destruction were examined. In the sham group, serum TNF-alpha, IL-17, and MDA levels increased, while SOD, CAT, GPx levels, and the expressions of Nrf2 and HO-1 decreased. On the other hand, in the EGCG administered groups, serum TNF-alpha, IL-17, and MDA levels improved, while SOD, CAT, GPx levels and the expressions of Nrf2 and HO-1 increased. Moreover, histopathological analysis has shown that perisynovial inflammation and cartilage-bone destruction decreased in the EGCG administered groups. These results suggest that EGCG has an antiarthritic effect by regulating the oxidative-antioxidant balance and cytokine levels in the CIA model, which is a surrogate experimental model of rheumatoid arthritis.
Keywords: collagen-induced arthritis; epigallocatechin 3-gallate; rheumatoid arthritis